Pengaruh Budaya Organisasi Dan Kualitas Sdm Terhadap Kinerja Pegawai Pada Sekretariat Daerah Kabupaten Pringsewu - Rosdiana, Dina; Ahmaludin, Ahmaludin (Utami Publisher, 2025)
The implementation of government must be seen in the context of optimizing the implementation of its main functions towards the existence of the apparatus in the government organization, especially in improving performance in order to provide services to the community. A government is considered effective if it can achieve its goals optimally, is able to adapt to its environment and can improve work performance and human resource development. For this reason, all government institutions must improve their performance including the Regional Secretariat of Pringsewu Regency. Various efforts can be made to improve employee performance starting from education and training, compensation so that there are awards for work achievements achieved. However, employee performance is not only influenced by these factors, but theoretically is also influenced by organizational culture and the quality of human resources owned by the agency. The purpose of this study is to determine: 1. The effect of organizational culture on employee performance 2. The effect of HR quality on employee performance 3. The effect of organizational culture and HR quality together on employee performance at the Regional Secretariat of Pringsewu Regency. This study uses a quantitative descriptive research method, namely a research method that uses data in the form of numbers in analyzing the facts found which aims to determine the relationship between variables in a population. The analysis used is simple and multiple regression. This study used 53 respondents. Based on the results of data analysis, the answers to the hypothesis were found as follows; There is an influence of organizational culture (X1) on employee performance (Y) at the Pringsewu Regency Regional Secretariat, with an influence level (R-square) of 83.9%. There is an influence of HR quality on employee performance at the Pringsewu Regency Regional Secretariat with an influence level of 86.9%. There is an influence of organizational culture and HR quality together on employee performance at the Pringsewu Regency Regional Secretariat, with an influence level of 94.3%.